Etiopathogenesis of Behcet's syndrome: Recent developments and current controversies - (:unkn) unknown (My University, 1999)
Genetic, infectious and immune dysfunctions are implicated in the etiopathogenesis of Behcet's Syndrome (BS). Histopathological studies reveal mixed cellular infiltrations consisting of mostly T lymphocytes, monocyte-macrophages and neutrophils. Although a viral etiology is also suggested, atypical streptoccocci (Strep Sanguis, Salivarius etc) is the most investigated. Increased proinflammatory and Th1 type cytokines such as TNF-α, IFN-γ, IL-2, IL-6 and IL-8 are found to be increased in the sera and in vitro culture supernatants. A controversial point is whether neutrophils are primarily defective (hyper-reactive) or activated due to the cytokine profile. Streptoccocal proteins such as KTH-1 or 65 kD mycobacterial heat shock protein (HSP) and its cross-reactive human homologue are shown to cause T and B cell responses in patients with BS. Both CD4+ and γδ T cells are activated with antigen-specific oligoclonal expansions and increased secretions of IFN-γ, IL-8 and TNF-α. The link with HLA-B51 which is present as a susceptibility or a severity marker of BS, is suggested to be related to neutrophil hyperreactivity with increased neutrophil burst responses also in HLA B51 transgenic animals. T cell responses to an HLA-B51 derived peptide and its retinal-S antigen homologue in posterior uveitis patients suggest that auto-immune responses might also be relevant. The same peptides are linked to uveitis also in rats and imply that different manifestations of BS may be related to various and possibly organ-specific antigens.
Keywords: Behcet's syndrome; Immune reponse